Institutionalist Perspectives on Development A Multidisciplinary Approach - Vliamos, Spyros; Zouboulakis, Michel S. (Palgrave Studies in Democracy, Innovation, and Entrepreneurship for Growth, 2018)
XXVI, 271 p. 17 illus.